2022
DOI: 10.1021/acs.jafc.1c07646
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of a Novel Myrosinase Rmyr fromRahnella inusitatafor High-Level Preparation of Sulforaphene and Sulforaphane

Abstract: Myrosinase is a biotechnological tool for the preparation of sulforaphane and sulforaphene with a variety of excellent biological activities. In this study, a gene encoding the novel glycoside hydrolase family 3 (GH3) myrosinase Rmyr from Rahnella inusitata was heterologously expressed in Escherichia coli BL21 (DE3). The purified Rmyr shows the highest activity at 40 °C and pH 7.0; meanwhile, its half-life at 30 °C reaches 12 days, indicating its excellent stability. Its sinigrin-, glucoraphenin-, and glucorap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 48 publications
4
22
0
Order By: Relevance
“…For instance, the optimal pH for TGG1, Cmyr, and ArMY2 are 5.5, 6.0, and 5.0, respectively [ 23 , 28 , 29 ]. As shown in Figure 3 c, metal ions (1 mM), including Zn 2+ , Mg 2+ , Ag + , Fe 3+ , Cu 2+ , Ba 2+ , K + , Ca 2+ , Pd 2+ , and Co 2+ , inhibited Smyr37 activity, which was consistent with the characteristics of the plant myrosinase and bacterial myrosinase Rmyr [ 14 ]. These results indicated that Smyr37 is a novel myrosinase with certain enzymatic properties different from those of the identified myrosinases.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…For instance, the optimal pH for TGG1, Cmyr, and ArMY2 are 5.5, 6.0, and 5.0, respectively [ 23 , 28 , 29 ]. As shown in Figure 3 c, metal ions (1 mM), including Zn 2+ , Mg 2+ , Ag + , Fe 3+ , Cu 2+ , Ba 2+ , K + , Ca 2+ , Pd 2+ , and Co 2+ , inhibited Smyr37 activity, which was consistent with the characteristics of the plant myrosinase and bacterial myrosinase Rmyr [ 14 ]. These results indicated that Smyr37 is a novel myrosinase with certain enzymatic properties different from those of the identified myrosinases.…”
Section: Discussionsupporting
confidence: 66%
“…The R . inusitata myrosinase Rmyr (69 kDa) exhibited good glucoraphanin-hydrolysis activity, and the optimum temperature and pH for the myrosinase activity were 40 °C and 7.0, respectively [ 14 ]. 6-phospho-β-glucosidase from E .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The suitability of long-term storage of endolysin XFII was tested in accordance with the method described by Wang et al, with minor modifications [ 52 ]. It was frozen at 4 °C for a few days and the residual bactericidal activity was determined by regularly sampling according to the standard assay, and the lysis curve of the storage date was obtained.…”
Section: Methodsmentioning
confidence: 99%